3-Dimensional dye sensitized solar cell sub-module with oblique angled cell array for enhanced power and energy density output utilizing non-linear relation in cosine law of light incident angle. (1st January 2019) - Yun, Min Ju; Sim, Yeon Hyang; Cha, Seung I.; Seo, Seon Hee; Lee, Dong Y.
Highlights: Flat panel design is not the best module design for many of solar cell systems. We have shown DSSCs' non-linearity came under angled incident light. The power output increased by 30–40% by arrayed the DSSCs cells with obliqued angle. Abstract: The application of photovoltaics (PV) has broadened into urban environments, which has different condition from rural environments, where generally PV power plants are installed. In order to develop solar cells for urban application, we should find the answers to two questions with dye-sensitized solar cells (DSSCs). One is current flat module design is really optimized for all solar cell types. The other is, if not, how to find the optimized module design. The power output from solar cells according to light incident angle has two types: one is linear to cosine law where the flat module and the other is non-linear to cosine law where 3-dimensional array of cell in the module can provide improved power output and energy density in given installed area. We have shown that DSSCs belongs to second case and non-linearity came under angled incident light by means of FDM calculation and experiments. In addition, by introducing patterns in the photoanode, light trapping effect maximized non-linearity to the oblique incident. We have arrayed the DSSCs cells into sub-modules with oblique angle. From this simple modification, from flat 2-dimensional array to 3-dimensional array of cells, the power output and energy density increased by 30–40%, respectively.